A new species of Weiseronyssus Samsinak 1962 (Acari: Mesostigmata: Diplogyniidae) from Iran, with a key for genera - Kazemi, Shahrooz; Klompen, Hans; Moraza, María L.; Kamali, Karim; Saboori, Alireza (Zootaxa, 2008)
A new species of Weiseronyssus (Mesostigmata: Diplogyniidae) is described from adult females and males taken from Oryctes nasicornis (L.) (Coleoptera: Scarabaeidae) in northern Iran. The genus was previously known from a single species associated with an undetermined dynastine scarab from southern China. The generic diagnosis is updated and a key to the genera of Diplogyniidae is presented.